Dynamic surface fault tolerant control for underwater remotely operated vehicles. (July 2018) - Baldini, Alessandro; Ciabattoni, Lucio; Felicetti, Riccardo; Ferracuti, Francesco; Freddi, Alessandro; Monteriù, Andrea
Abstract: In this paper, we present a two stages actuator Fault Tolerant Control (FTC) strategy for the trajectory tracking of a Remotely Operated Vehicle (ROV). Dynamic Surface Control (DSC) is used to generate the moment and forces required by the vehicle to perform the desired motion. In the second stage of the control system, a fault tolerant thruster allocation policy is employed to distribute moment and forces among the thrusters. Exhaustive simulations have been carried out in order to compare the performance of the proposed solution with respect to different control techniques (i.e., PID, backstepping and sliding mode approaches). Saturations, actuator dynamics, sensor noises and time discretization are considered, in fault-free and faulty conditions. Furthermore, in order to provide a fair and exhaustive comparison of the control techniques, the same meta-heuristic approach, namely Artificial Bee Colony algorithm (ABC), has been employed to tune the controllers parameters. Highlights: A fault tolerant control scheme for remotely operated vehicles is proposed. The scheme combines fault tolerant thrust allocation and dynamic surface control. The scheme is compared with different control approaches in a realistic simulation. Thruster fault/failure tolerant trajectory tracking is achieved.